Direct Power Control of Brushless Doubly-fed Induction Generator Used in Wind Energy Conversion System - A. Rahab; F. Senani; H. Benalla (Institute of Advanced Engineering and Science, 2017)
This article describes firstly a wind power production line, principally a wind turbine constitutes her and brushless doubly fed induction generator (BDFIG). The models of these components are developed, and control objective of BDFIG is to achieve a dynamic performance similar to the doubly fed induction generator (DFIG) using a stator flux field oriented control (FOC) and direct power control (DPC) strategy. After, the simulation program using Matlab/Simulink has been developed. The performances of this strategy are evaluated and analyzed, so the results show a good robustness great dynamic and a precision of speed.